Exploring the Cultural Ecological Awareness in the Ola Ma Farming Cycle of the Lewotala Indigenous Community - Ritan, Germana Oreng; Lemba, Vinsensius (Unika Santu Paulus Ruteng, 2025)
This study examines the ecological awareness of the Lewotala Indigenous community as expressed through the Ola Ma farming cycle—a culturally grounded framework that underpins the community's unique relationship with nature, vital for both their survival and environmental preservation. The primary aim is to describe the Ola Ma farming cycle and analyze the aspects of cultural ecological awareness it embodies. The research investigates the community's perceptions and attitudes toward their natural environment as well as their strategies for fostering sustainable human–nature interactions. Employing a qualitative methodology with an ethnoecological approach, data were gathered through systematic observations, in-depth interviews, and focus group discussions. Data analysis followed the Miles and Huberman interactive model, which encompasses data reduction, display, and conclusion drawing. The findings indicate that the Ola Ma farming cycle is conducted according to the Tonu Wujo Calendar—a traditional, orally transmitted twelve-month calendar based on indigenous computational methods. Moreover, two distinct models emerged in the community's understanding of nature: a vertical model reflecting their relationship with a Supreme Being and a horizontal model characterizing their direct engagement with the natural world. Both models underscore the importance of a nature-based lifestyle as a cornerstone for building and maintaining sustainable human–environment relationships. Consequently, the ecological awareness inherent in the Ola Ma farming practice is crucial for cultivating, nurturing, and safeguarding nature, ensuring the continuity of both human life and the natural ecosystem. Sustaining and enhancing this awareness will require multifaceted strategies and the active engagement of diverse stakeholders.